Ameliorating the in vivo antimalarial efficacy of artemether using nanostructured lipid carriers. (17th February 2018) - Vanka, Ravisankar; Kuppusamy, Gowthamarajan; Praveen Kumar, Simhadri; Baruah, Uday Krishna; Karri, Veera Venkata Satyanarayana Reddy; Pandey, Vimal; Babu, Phanithi Prakash
Abstract: Cerebral malaria (CM) is a fatal neurological complication of Plasmodium falciparum infection that affects children (below five years old) in sub-Saharan Africa and adults in South-East Asia each year having the fatality rate of 10–25%. The survivors of CM also have high risk of long term neurological or cognitive deficits. The objective of the present investigation was to develop optimised nanostructured lipid carriers (NLCs) of artemether (ARM) for enhanced anti-malarial efficacy of ARM. NLCs of ARM were prepared by a combination of high speed homogenisation (HSH) and probe sonication techniques. Preliminary solubility studies for ARM showed highest solubility in trimyristin (solid lipid), capmul MCM NF (liquid lipid) and polysorbate 80 (surfactant). Trimyristin and capmul showed superior miscibility at a ratio of 70:30.The optimised NLC formulation has the particle size (PS) of: 48.59 ± 3.67 nm, zeta potential (ZP) of: −32 ± 1.63 mV and entrapment efficiency (EE) of: 91 ± 3.62%. In vitro cell line (human embryonic kidney fibroblast cell line (HEK 293 T)) cytotoxicity studies showed that prepared formulation was non-toxic. The results of in vivo studies in CM induced mice prevented the recrudescence of parasite after administration of NLCs of ARM. Additionally, NLCs of ARM showed better parasite clearance, higher survival (60%) in comparison to ARM solution (40%). Also it was observed that lesser entrapment of Evans blue stain (prepared in PBS as solution) in the NLCs of ARM treated brains of C57BL/6 mice than ARM solution treated mice. Hence NLCs of ARM may be a better alternative for improving therapeutic efficacy than ARM solution.